Improving the Quality of Guest Room Cleaning Services at Conrad Bali Resort & Spa - Ariana, I Gede Gita; Adi, Ida Ayu Sri Puspa; Darmaputra, Putu Gede Eka (Journal of Tourism and Hospitality Analysis (JoTHA), 2025)
This study aims to analyse the role and strategies of room attendants in improving the quality of guest room cleaning services at Conrad Bali Resort & Spa. A qualitative descriptive approach was employed, with data collected through direct observation, in-depth interviews with room attendants, supervisors, and the executive housekeeper, as well as documentation of housekeeping activities. The analysis was guided by the SERVQUAL model, encompassing five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy. The findings indicate that Conrad Bali Resort & Spa has generally implemented guest room cleaning procedures in accordance with established standards. Strengths were identified in equipment readiness, layered supervision, prompt response to guest complaints, and personalized service delivery. However, several inconsistencies were observed, particularly in equipment condition checks, bed-making accuracy, and bathroom cleanliness. To address these issues, the hotel applies various improvement strategies, including regular technical and ethical training, multi-level supervision, digital interdepartmental communication, and the integration of guest preference data into daily briefings. Overall, the study demonstrates that a combination of structured supervision, staff competency development, and personalized service practices contributes significantly to maintaining high standards of room cleanliness and enhancing guest satisfaction. These findings underline the importance of continuous service quality evaluation and adaptive housekeeping strategies in sustaining competitiveness within the luxury hospitality sector.